Pengaruh Brand Personality Terhadap Purchase Intention Produk The Body Shop - Lidia Adetiya Hermanto; Rodhiah Rodhiah (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2019)
This research was conducted to prove that Brand personality had a positive influence on the Purchase Intention of The Body Shop consumers. The sampling technique used was purposive sampling with the total of 100 respondents. Data collection using a questionnaire with a Likert Scale. In this study, the analysis technique uses Multiple Regression Analysis, Determination Coefficient and Hypothesis Testing using SPSS 25 Software. The results of this study show that Sincerity, Competence, Excitement, dan Sophistication of Brand personality have a positive effect on the Purchase Intention of The Body Shop consumers. Meanwhile, Ruggedness of Brand personality does not have a positive effect on the Purchase Intention of The Body Shop consumers.Penelitian ini dilakukan untuk membuktikan Brand personality memiliki pengaruh yang positif untuk Purchase Intention konsumen The Body Shop. Teknik pengambilan sampel yang digunakan adalah convenience sampling dengan jumlah sebanyak 100 responden. Pengumpulan data dengan menggunakan kuisioner dengan Skala Ordinal. Teknik analisis dalam penelitian ini menggunakan Analisis Regresi Berganda, Koefisien Determinasi dan Pengujian Hipotesis dengan menggunakan SPSS 25. Hasil penelitian ini menunjukkan bahwa Sincerity, Competence, Excitement, dan Sophistication dari Brand personality berpengaruh positif terhadap Purchase Intention konsumen The Body Shop, sedangkan Ruggedness dari Brand personality tidak berpengaruh positif terhadap Purchase Intention konsumen The Body Shop.